Basilar artery migraine and reversible imaging abnormalities. - Maytal, J; Libman, R B; Lustrin, E S (American Journal of Neuroradiology, 1998)
We report a case of a basilar artery migraine in a 17-year-old boy with transient CT and MR abnormalities after each of two migraine episodes. A repeat MR study 6 months after the last event showed complete resolution of the lesion. Transient abnormalities on brain images similar to those shown in our case have been reported in patients with migraine and other neurologic conditions and are most likely related to cerebral vasogenic edema.